Examining The Contribution Of Educational Institutions In Fostering Digital Media Literacy: An Analysis Of The Impact Of Curriculum Integration Of Digital Media Training On Students' Skill Development. - Saurabhi Shetye; Dr. Gayatri Indrakanti (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Digital Media Literacy plays a pivotal role in helping students assess the complexities of the wide virtual landscape. Educational Institutions have started incorporating various courses related to the same and are comprehensively focusing on improving the digital skill set of students. This research is based on a longitudinal study that measures the proficiency of students before starting with the course where in they are presented a questionnaire related to investigating students' attitudes towards digital media, their online habits, and their perceptions of the importance of media literacy and studies the changes noticed in the same, after ending the course. This paper aims to analyze and track the perception of students about digital media literacy and to assess their proficiency over an extended period of six months The findings of this study highlight that the digital literacy provided as a part of curriculum at various levels of education not only centers around the concept of digital literacy but also inculcates skills that transfer to real-life scenarios and subsequent academic or professional pursuits.